Good practices and problems with regard to the training of prison workers and the foreign prison population in Spain and Catalonia - Aranda Ocaña, Mónica (Crítica Penal y Poder, 2021)
This article is based on the preliminary results of the B-ComPetent: Boosting Competences in Penitentiary Staff in Europe project, concerning the good practices identified in different European countries with regard to the training of prison workers and the foreign prison population.